The Cambridge history of literary criticism / 4 The eighteenth century / ed. by H.B. Nisbet - Nisbet, Hugh Barr (The Cambridge history of literary criticism, 1997)
This is a comprehensive 1997 account of the history of literary criticism in Britain and Europe between 1660 and 1800. Unlike previous histories, it is not just a chronological survey of critical writing, but a multidisciplinary investigation of how the understanding of literature and its various genres was transformed, at the start of the modern era, by developments in philosophy, psychology, the natural sciences, linguistics, and other disciplines, as well as in society at large. In the process, modern literary theory - at first often implicit in literary texts themselves - emancipated itself from classical poetics and rhetoric, and literary criticism emerged as a full-time professional activity catering for an expanding literate public. The volume is international both in coverage and in authorship. Extensive bibliographies provide guidance for further specialised study
Keywords: Aufsatzsammlung; Geschichte 1700-1800; Literaturkritik; Europa